2011
DOI: 10.1093/her/cyr043
|View full text |Cite
|
Sign up to set email alerts
|

A media advocacy intervention linking health disparities and food insecurity

Abstract: Media advocacy is a well-established strategy for transmitting health messages to the public. This paper discusses a media advocacy intervention that raised issues about how the public interprets messages about the negative effects of poverty on population health. In conjunction with the publication of a manuscript illustrating how income-related food insecurity leads to disparities related to the consumption of a popular food product across Canada (namely, Kraft Dinner®), we launched a media intervention inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…, Rock et al . ), improving transportation infrastructure and addressing structural violence resulting from border security policy for underserved border (migrant) populations in the southern USA (Ingram et al . ); developing physical activity resources in low‐income neighbourhoods (García et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…, Rock et al . ), improving transportation infrastructure and addressing structural violence resulting from border security policy for underserved border (migrant) populations in the southern USA (Ingram et al . ); developing physical activity resources in low‐income neighbourhoods (García et al .…”
Section: Resultsmentioning
confidence: 99%
“…A smaller proportion of this literature describes policy advocacy initiatives that are directly related to addressing social determinants of health and reducing inequities in health, such as advocating for policies that ensure access to affordable healthy housing (Krieger & Higgins 2002, Plough 2013, addressing food security and built environment (Laraia et al 2003, Giang et al 2008, McIntyre 2011, addressing gendered and racial inequities in healthcare access (Dorfman 2003a, Zust & Moline 2003, Haq et al 2010, Okonofua et al 2011, Rock et al 2011, improving transportation infrastructure and addressing structural violence resulting from border security policy for underserved border (migrant) populations in the southern USA (Ingram et al 2014); developing physical activity resources in low-income neighbourhoods (Garc ıa et al 2009), reduce tobacco-related disparities (Garcia et al 2015) and promoting environmental justice (Kreger et al 2011, McAndrews & Marcus 2014. We could find no examples of advocacy by the public health sector for broad income security or poverty reduction initiatives such as a campaign for a living wage or guaranteed minimum income.…”
Section: Limited Evidence Of Public Health Advocacy For Equity/socialmentioning
confidence: 99%
“…The second theory pertains to news media as framer. 24,25,28,29 According to this theory, the ways in which issues are covered (e.g., placing emphasis on certain aspects of a story, repeated coverage, tone) shape how those issues are perceived and corresponding responses to them.…”
Section: Methodology and Theoretical Frameworkmentioning
confidence: 99%
“…33 In their participatory action research with women in Nova Scotia, Williams and colleagues 34–36 have demonstrated innovative approaches to conducting research with women experiencing food insecurity (structured dialogue and food costing) and identified unique gendered dimensions of food insecurity that are exacerbated by public policy in what they call “milk insecurity.” 37,38 Hamelin and colleagues 39,40 found multiple domains related to the social implications of food insecurity that influence both individual and family well-being. Rock and colleagues 41,42 investigated the “discomforting” physical and psychological emotions associated with having to eat in a manner outside of the experience of food secure households. Carney’s 43 analyses from work with Mexican immigrant women in California provide provocative insights regarding the gendered and political (immigration-related) dimensions of food as a human right.…”
Section: Food Insecurity As Social Processmentioning
confidence: 99%